Government in America : people, politics, and policy - Lineberry, Robert L.; Edwards, George C. (Glenview, Ill. : Scott, Foresman, 1989)
Lineberry argues that U.S. politics centers around equality, the political economy, and technology, and that it seeks to incorporate global, technological, and ethical issues in the American political landscape. He focuses on four theories of American politics: democratic theory, class and elite theory, pluralism, and hyperpluralism. New to this edition are comparisons with other governments and chapters on the role of media in shaping public opinion. ISBN 0-673-39898-6: $20.00.
Includes bibliographical references and index.
Keywords: Politics and government; Politisches System; United States -- Politics and government; USA; United States -- Politics